Modèle énergétique uniboite de la croissance des huîtres (Crassostrea gigas) dans le bassin de Marennes-Oléron - Bacher, Cedric; Heral, Maurice; Deslous-paoli, Jean-marc; Razet, Daniel (Canadian Journal of Fisheries and Aquatic Sciences, 1991)
The growth of oysters (Crassostrea gigas) is modeled in order to study the trophic capacity of the Bay of Marennes Oléron. Total seston and amount of protids, lipids, and carbohydrates converted to energy are the environmental factors taken into account. Time series of these variables are derived during 2 yr with a daily time step from a linear regression including the tidal velocity, the height of the water column, and the wind velocity. A model of the energetic budget based on assimilation and respiration terms and depending on the previous time series is run to simulate the individual growth of an oyster. The knowledge of the number of oysters, the flow of water entering the bay, and the volume of the bay allows us then to estimate that 7% of the available energy is used by the population. The number of individuals is given theoretical values to show that the impact of the amount of oysters on the growth of an individual is nonnegligible. The trophic capacity of the bay is then defined and it is pointed out that more information may be expected from a model coupling the transport of particulate matter and the growth of oysters. Un modèle de croissance des huîtres (Crassostrea gigas) dans le bassin de Marennes-Oléron est élaboré afin d'étudier la notion de capacité trophique. Les facteurs environnementaux pris en compte sont le seston total et la somme des équivalents énergétiques des protides, lipides et glucides de la colonne d'eau. Leur évolution temporelle sur 2 ans est reconstituée avec un pas de temps journalier à l'aide d'un modèle régressif fonction du courant de marée, de fa hauteur d'eau et de la force du vent. A partir de ces séries, un modèle de bilan énergétique, comprenant un terme d'assimilation et un terme de respiration, est construit pour simuler la croissance d'une huître pendant 2 ans. Connaissant le nombre d'individus dans le bassin, le débit entrant et le volume moyens des masses d'eau dans le bassin, ce modèle permet d'estimer à 7 % le pourcentage d'énergie utilisée par la population. ...